A Content Analysis on Sri Lankan English Morphological Processes Identifiable in Short Stories: A Study Based on Selected Eight Short Story Collections Written by Sri Lankan Authors - Amarasiri, K.W.Y.S. (University of Jaffna, 2025)
Standard Sri Lankan English is a unique variety that has distinctive features that differ from the other varieties of English. These distinctive characteristics can be identified in various linguistics domains including morphology, phonology, syntax and semantics. Thus, the current study focuses on morphological processes that differentiate the vocabulary from Standard English. Limited research studies have been conducted to determine the morphology of Sri Lankan English, particularly with reference to the Sri Lankan English literary texts. Hence, the purpose of this study was to investigate the Sri Lankan English morphological processes identifiable in short story collections by Sri Lankan authors which distinguish the variety from standard British and American English. The data of the present study was collected utilizing a purposive sample of eight Sri Lankan English short story collections that have won or been nominated for the Gratiaen Prize from 1993 to the present. The methodology incorporated in the present study was content analysis through which data was analyzed according to the theoretical framework built based on the research findings of the scholars; Gunasekera (2005) and Senarathna (2009). The present study reveals that Sri Lankan English short stories have incorporated morphological processes like borrowings, compounds, acronyms, reduplications, expressions, tags, clippings, abbreviations, and back formations. Simultaneously, the study’s findings also indicate that, among the above morphological processes, borrowings are Sri Lankan English’s most productive morphological process. Subsequently, this study will contribute to the knowledge of the field of Sri Lankan English morphology.
Keywords: Sri Lankan English; Sri Lankan English morphological processes; Sri Lankan English short stories; Content analysis